2011
DOI: 10.1128/jvi.02609-10
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Polyomavirus Middle T Antigen in the Mouse Prostate Gives Rise to Carcinoma

Abstract: The middle T (MT) antigen of polyomavirus has provided fundamental insights into the regulation of mammalian cell growth in vitro and important animal models for the analysis of tumor induction. The mouse mammary tumor virus (MMTV)-MT model of breast cancer has been important for probing the cellular signaling pathways in mammary tumorigenesis. MT itself has no intrinsic enzymatic activity but, rather, transforms by binding to and activating key intracellular signaling molecules, phosphatidylinositol 3-kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…7B). The R221a cells express the middle T oncoprotein, a strong driver of constitutive PI3K/Akt and Src kinase activity, which would be unaffected by LY294002 treatment [25]. These results confirm previous reports that activation of Akt in response to IL4 is cell type/context dependent [5, 12].…”
Section: Discussionsupporting
confidence: 88%
“…7B). The R221a cells express the middle T oncoprotein, a strong driver of constitutive PI3K/Akt and Src kinase activity, which would be unaffected by LY294002 treatment [25]. These results confirm previous reports that activation of Akt in response to IL4 is cell type/context dependent [5, 12].…”
Section: Discussionsupporting
confidence: 88%
“…Previous work from our laboratories showed that prostate-specific expression of polyomavirus MT in the mouse leads to prostate intraepithelial neoplasia (PIN) in the dorsolateral prostate (DLP) and ventral prostate (VP) lobes. This phenotype can be observed in animals as young as 8 weeks of age and progresses throughout the animal's lifetime, ultimately leading to invasion (10).…”
Section: Resultsmentioning
confidence: 99%
“…As noted earlier, MT tumorigenesis in the breast requires p110␣. We have recently reported a prostate cancer model driven by wildtype MT (10). Here we demonstrate the pivotal role of the PI3K pathway by showing that the loss of PI3K signaling causes significantly delayed tumor growth.…”
mentioning
confidence: 91%
“…And the transcriptional activities of p65 and IkBa genes in infected prostate epithelial cells were significantly higher than those in uninfected cells, indicating that the NF-kB signaling pathway was involved in the occurrence of prostate cancer in the early stage of inflammation, and the activation of NF-kB was time-dependent with the stimulation of inflammation (68,73). In an animal experiment, mice infected with polyomavirus developed prostatic intraepithelial neoplasia on the ventral and dorsal sides of the prostate, and transcriptional map analysis showed regulation of multiple pathways, including NF-kB (87). In other words, the use of some means to regulate the activity of NF-kB may lead to the loss of the cancerous potential of prostate cells.…”
Section: Inflammatory Pathway Of Prostate Microbiota (Indirect Pathway)mentioning
confidence: 99%